Analysis of Factors Related to Employee Satisfaction at Rural HealthCenters in Samarinda - Ashri Budi Astuti; Ratno Adrianto; Irfansyah Baharuddin pakki (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Job satisfaction is an important goal in Human Resources management because it directly and indirectly impacts work productivity. Employee job satisfaction directly impacts organizational commitment, where employees who are satisfied with their work, colleagues, pay, and superiors are more likely to be highly dedicated to the organization Objective : The purpose of this study was to analyze factors related to employee job satisfaction at Rural Community Health Centers in Samarinda. The research method used was quantitative with a cross-sectional approach. The study population consisted of 179 employees, and the sample size was determined by purposive sampling, with 138 employees. Data were collected using a questionnaire with a Likert scale Results : The results of the bivariate analysis showed a relationship between income and job satisfaction among Rural Community Health Center employees in Samarinda, with a p-value of 0.00. In addition, the work policy variable also shows a relationship with job satisfaction with a p value of 0.00. Conclusion/Lesson Learned : There is a relationship between income and work policies with employee job satisfaction in rural community health center employees in Samarinda.